Massive aortic root aneurysm in an infant with the Loeys–Dietz syndrome. (13th June 2017) - Molina-Sánchez, Tatiana; Calderón-Colmenero, Juan; Sandoval, Juan Pablo
Abstract: A 10-month-old girl with type I Loeys–Dietz syndrome developed a conspicuous aortic root aneurysm that was well demonstrated on chest X-ray/CT reconstruction. She underwent successful valve-spare repair of the ascending aorta.